Antecedents of Customer Satisfaction - Leninkumar, Vithya (Archives of Business Research, 2019)
Survival of any business lies in the relationship it has with the customers where the customer satisfaction plays a major role in attracting and retaining the customers. When a business want to be successful and to gain competitive advantage the identification of antecedents of customer satisfaction is indispensable. Thus, this study attempts to focus on key antecedents of customer satisfaction in commercial banking set up in Northern Sri Lanka. The population consisted of customers of Commercial Banks in Northern Sri Lanka and the sample of 350 respondents were selected based on convenience sampling method among which 267 were used for further analysis. The data were analysed using SPSS version 21.0. The findings revealed a significant positive relationship between the service quality and customer satisfaction; perceived value and customer satisfaction; customer trust and customer satisfaction and customer trust and bank image.